Implementation of fuzzy in DQ control of PV based inverter with plug-in electric vehicles - Hanumesh, Hanumesh; Ponnusamy, Arul; Selvaraj, Dhamodharan; Shankaregowda, Tanuja Koppa; Narasimhachar, Venugopal; Halasiddappa, Ananda Marilingappa (Institute of Advanced Engineering and Science, 2025)
In modern power systems, photovoltaic (PV) generation plays a vital role in sustainable energy supply. PV systems generate DC power, which is converted to AC using built-in converters for grid integration. The quality of power injected into the grid is crucial, especially in the presence of plug-in electric vehicles (PEVs) and non-linear loads, which introduce harmonics and dynamic disturbances. To enhance power quality, advanced control strategies are employed. This paper presents a comparative study of direct-quadrature (DQ) control techniques using traditional proportional-integral (PI) controllers and fuzzy logic controllers (FLCs) in a grid-connected PV system. The DQ control method simplifies the regulation of active and reactive power by transforming three-phase signals into a rotating reference frame. While PI controllers are widely used, they often struggle with non-linearities and load variations. FLCs, on the other hand, offer adaptive control without requiring precise mathematical models, making them more effective under dynamic conditions. The system under study includes PV generation, PEVs, and non linear loads. Performance metrics such as total harmonic distortion (THD), voltage stability, and power factor are analyzed. Results show that fuzzy controllers significantly improve power quality and system response.